At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

1+3+5+7+...+25 is subtracted from 2+4+6+8+...+26. The answer is​

Sagot :

[tex]S_1 = 2+4+6+8+...+26 \\\\~~~~=2(1+2+3+4+...+13)\\\\~~~~=2 \cdot \dfrac{13(13+1)}2~~~~~~~~;\left[\text{Sum of consecutive positive integers }= \dfrac{n(n+1)}2 \right] \\\\~~~~=13 \cdot 14\\\\~~~~=182\\\\S_2 = 1+3+5+7+...+25\\\\\text{It is an arithmetic series wihere}\\\\\text{First term, a =1, ~Common difference, d = 2,~ number of terms = n} \\\\~~~~\text{Nth term} = a+(n-1)d\\\\\implies 25 = 1+(n-1)2\\\\\implies 2n-2 = 24\\\\\implies 2n = 24+2\\\\\implies 2n= 26\\\\[/tex]

[tex]\implies n = \dfrac{26}2 \\\\\implies n= 13\\\\\text{S} _2= \dfrac{\text{n(First term+ Last term)}}{2}\\\\~~~~~~=\dfrac{13(1+25)}2\\\\~~~~~~=\dfrac{13 \times 26}2\\\\~~~~~~=13 \times 13\\\\~~~~~~=169\\\\\text{Hence,}~~ S_1 - S_2 =182 - 169 =13[/tex]

Answer:

13

Step-by-step explanation:

2 + 4 + 6 + 8 + ...... + 26

n = 13

Sum of first 'n' even numbers = n( n +1)

                                                 = 13 * 14

                                                  = 182

1 + 3 + 5 + 7 + .....+25

n = 13

Sum of first 'n' odd numbers = n²

                                               = 13 * 13

                                               = 169

2 + 4 + 6 + 8 + ... + 26 - (1 + 3 + 5 + 7 + ......+25) = 182 - 169

                                                                            = 13